2023
DOI: 10.3171/2022.11.spine22875
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to DEXA for the assessment of bone density: a systematic review of the literature and future recommendations

Abstract: OBJECTIVE Osteoporosis has significant implications in spine fusion surgery, for which reduced spinal bone mineral density (BMD) can result in complications and poorer outcomes. Currently, dual-energy x-ray absorptiometry (DEXA) is the gold standard for radiographic diagnosis of osteoporosis, although DEXA accuracy may be limited by the presence of degenerative spinal pathology. In recent years, there has been an evolving interest in using alternative imaging, including CT and MRI, to assess BMD. In this syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Low BMD poses a significant risk for fractures and falls, leading to considerable financial, physical, and psychosocial burdens on patients and impacting overall prognosis. While DXA remains the gold standard for BMD assessment, [9] there has been growing interest in alternative imaging modalities such as CT. CT scans offer the advantage of indirectly estimating BMD from HU measured on opportunistic scans of the abdomen, providing a preliminary screening tool to evaluate the necessity for a DXA scan in the clinical diagnosis of osteoporosis. For example, Cohen et al demonstrated in their study that an HU ≤ 110 indicates a high likelihood of abnormal BMD (osteoporosis or osteopenia), prompting further DXA examination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low BMD poses a significant risk for fractures and falls, leading to considerable financial, physical, and psychosocial burdens on patients and impacting overall prognosis. While DXA remains the gold standard for BMD assessment, [9] there has been growing interest in alternative imaging modalities such as CT. CT scans offer the advantage of indirectly estimating BMD from HU measured on opportunistic scans of the abdomen, providing a preliminary screening tool to evaluate the necessity for a DXA scan in the clinical diagnosis of osteoporosis. For example, Cohen et al demonstrated in their study that an HU ≤ 110 indicates a high likelihood of abnormal BMD (osteoporosis or osteopenia), prompting further DXA examination.…”
Section: Discussionmentioning
confidence: 99%
“…Using a cutoff point of 110 HU, as defined by Cohen et al, HU values were dichotomized into abnormal BMD (≤110 HU) and normal BMD (>110 HU) categories. [9,14] Among the patient cohort, 114 (23.8%) individuals were categorized in the abnormal BMD group, while 364 (76.2%) individuals were classified in the normal BMD group. Although our cohort was dichotomized using the well-known cutoff point of 110 HU, it is noteworthy that this value is very close to the 25th percentile (113 HU) of the entire cohort, which is one of the recommended cutoff values for dichotomizing cohorts in clinical studies.…”
Section: Analysis Of Abdominopelvic Ct Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…While CT is ideal for evaluating the extent and severity of bone loss, it exposes the patient to ionizing radiation and is more expensive than conventional radiography. MRI, however, does not expose the patient to ionizing radiation and is better suited for evaluating soft tissues and bone marrow, but it has limited spatial resolution and may not provide sufficient details for assessing bone density [13]. Quantitative measures of bone density, such as bone mineral density (BMD) using dual-energy X-ray absorptiometry (DXA) or other specialized techniques, are certainly not sensitive enough for the skull.…”
Section: Introductionmentioning
confidence: 99%
“…One issue is that it can produce artifacts from implants or degenerative changes, such as subchondral sclerosis, osteophyte formation, vertebral compression fractures, and soft tissue calcification, which often coexist in elderly patients with low bone mass. 6,7 Additionally, DEXA is a two-dimensional evaluation method that cannot differentiate between cancellous and cortical bones. This distinction is important because the cancellous bone may be more indicative of vertebral fracture risk than the cortical bone.…”
mentioning
confidence: 99%